Success for All: A Quantitative Synthesis of U.S. Evaluations. Issue 1 (2nd January 2021) - Cheung, Alan C. K.; Xie, Chen; Zhuang, Tengteng; Neitzel, Amanda J.; Slavin, Robert E.
Abstract: Success for All (SFA) is a comprehensive whole-school approach designed to help high-poverty elementary schools increase the reading success of their students. It is designed to ensure success in grades K-2 and then build on this success in later grades. SFA combines instruction emphasizing phonics and cooperative learning, one-to-small group tutoring for students who need it in the primary grades, frequent assessment and regrouping, parent involvement, distributed leadership, and extensive training and coaching. Over a 33-year period, SFA has been extensively evaluated, mostly by researchers unconnected to the program. This quantitative synthesis reviews the findings of these evaluations. Seventeen US studies meeting rigorous inclusion standards had a mean effect size of +0.24 ( p  < .05) on independent measures. Effects were largest for low achievers (ES= +0.54, p  < .01). Although outcomes vary across studies, mean impacts support the effectiveness of Success for All for the reading success of disadvantaged students.